Measurable residual disease in hairy cell leukemia: Technical considerations and clinical significance - Robak, Tadeusz; Robak, Paweł (Frontiers in Oncology, 2022)
Hairy cell leukemia (HCL) is a rare type of chronic lymphoid leukemia originating from a mature B lymphocyte. A diagnosis of HCL is based on cytology, confirmed by multiparametric flow cytometry (MFC) studies using anti-B-cell monoclonal antibodies, together with a panel of antibodies more specific to HCL, such as CD11c, CD25, CD103 and CD123. Recently, the BRAF V600E mutation has been described as a disease-defining genetic event. Measurable residual disease (MRD) is defined as the lowest level of HCL cells that can be detected accurately and reproducibly using validated methods; as MRD negativity is associated with high rates of durable complete response, by clearing MRD, the long-term outcome may be improved in patients with advanced HCL. MRD is typically detected using bone marrow, and in some cases, peripheral blood; however, in HCL, discrepancies frequently exist between MRD results obtained from blood, bone marrow aspirate and core biopsy. Among the methods used for MRD detection, MFC appears to be a more sensitive technique than immunohistochemistry. Molecular tests are also used, such as real-time quantitative PCR for unique immunoglobulin heavy chain (IgH) gene rearrangements and PCR techniques with clone specificity for BRAF V600E. Clone-specific PCR (spPCR) is able to detect one HCL cell in 106 normal cells, and is particularly suitable for patients found to be negative for MRD by MFC. Recently, the Hairy Cell Leukemia Consortium created a platform to work on a definition for MRD, and establish the optimal time point, tissue type and method for measuring MRD. This